Analisis Komitmen Kerja Pegawai di Badan Pusat Statistika Karawang - Melly Maryana; Uus Md Fadli (Politeknik Kampar, 2024)
The Karawang Central Statistics Agency (BPS) is a government agency that has a strategic role in providing accurate and reliable statistical data and information. To be able to carry out this function properly, BPS Karawang needs employees who have a high work commitment. However, based on preliminary data, there are indications that the work commitment of employees at BPS Karawang has not been optimal. This study aims to analyze the work commitment of employees at the Karawang Central Statistics Agency (BPS Karawang) and the factors that affect organizational performance. The results of the study show that affective and normative commitment have a significant effect on employee performance, while continuous commitment has no significant effect. Affective commitment refers to an employee's emotionality, identification, and engagement with the organization, which influences their behavior toward the tasks they receive. Normative commitment, on the other hand, relates to the employee's feelings towards the tasks assigned to the organization and the organization's values are the same as the employee's personal values. This study uses a qualitative method and involves interviews with 5 respondents, including a head of agency and 4 employees. Data analysis was carried out using thematic analysis and narrative analysis. The results of this study are expected to be the basis for BPS Karawang in developing strategies and policies to increase employee work commitment, so that it can support the achievement of organizational goals optimally.